ENGLISH TEACHERS' CHALLENGES IN TEACHING ENGLISH TO 3-5 YEARS OLD CHILDREN AT PPA HILINA'A - Zebua, Meniati; Laoli, Adieli; Waruwu, Merlin; Waruwu, Julvin Oryentika; Halawa, Fitri Seniawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teaching English to children aged 3–5 years presents unique challenges related to their developmental characteristics, particularly in non-formal early childhood education settings. This study aims to explore the challenges faced by English teachers in teaching young learners at PPA Krammer Hilina'a. A descriptive qualitative research design was employed to obtain an in-depth understanding of classroom practices and teacher experiences. Data were collected through semi-structured interviews and classroom observations involving one teacher/student practitioner responsible for teaching English for Young Learners (EYL). The data were analyzed thematically to identify key challenges and instructional responses. The findings reveal that teachers face significant pedagogical difficulties, including children’s limited ability to understand abstract concepts, rapid memory loss, and interference from the first language (L1). Classroom management emerged as the most prominent challenge, characterized by short attention spans, high energy levels, and ineffective transitions between learning activities. To address these challenges, teachers implemented visual-based learning strategies, such as flashcards and presentation slides, combined with emotional and patient interaction and direct engagement with students. These approaches contributed to improved learner participation and confidence. The study concludes that teaching English to very young learners in non-formal educational contexts requires developmentally appropriate strategies and strong classroom management skills. Therefore, targeted training in early childhood pedagogy and English for Young Learners is recommended to enhance teaching effectiveness.